Pengaruh Penguasaan Kosakata Dan Tata Bahasa Terhadap Menulis Bahasa Inggris - Sri Mulyati (LPPM Universitas Bina Sarana Informatika, 2015)
This study is a survey research. The aims are to find and analyze empirically the effects of vocabulary and grammar mastery toward students’s English writing skill. The population are students of Pamulang University, Tangerang, with the result that 60 respondents used as sample in this research. The research sample were obtained from simple random sampling method, that is the researcher mixing the subjects in the population so that all subjects are considered equal. The research design used by correlation techniques with three variables consisting of two independent variables, that is vocabulary and grammar mastery, and one dependent variable, that is English writing skill. Data collection was done by using a questionnaire and then taking the score. The collected data then analyzed by using correlation and multiple linear regression technic. Before the data is analyzed, firstly test the data requirements (normality and linearity tests), and descriptive statistical analysis. The research result showed that: 1). Found the significant influence of vocabulary and grammar mastery concurrently toward students’s English writing skill, where Fhitung= 163,056 > Ftable = 3, 16 and Sig = 0,000 < 0,05. 2). Found the significant influence of vocabulary mastery toward students’s English writing skill, where thitung = 5,334 > ttable = 2,00 and Sig = 0, 000, and 3). Found the significant influence of grammar mastery toward students’s writing skill, where thitung = 4,889 and Sig = 0,000. It means that students’s writing skill were affected by vocabulary and grammar mastery.